2023
DOI: 10.3389/fpubh.2023.1167537
|View full text |Cite
|
Sign up to set email alerts
|

Social integration, physical and mental health and subjective well-being in the floating population—a moderated mediation analysis

Abstract: BackgroundIndividuals of domestic migrant populations in China (specifically, migration that is economically driven) often face difficulties in social integration. They are suffering from discrimination and unfair treatment in work and life, which do harm to their physical/mental health and Subjective Well-Being (SWB).MethodsThe current study utilized a stratified sampling survey in the Yangtze River Delta region of China, in October and November 2022. Six hundred and eleven useful self-reported questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Indeed, it can significantly impact health outcomes through social mentality and perceived stress ( Xia & Ma, 2020 ; Zhou et al, 2022 ). Previous research further found that social integration can also improve migrants' physical health via increasing utilization of health services ( Fei et al, 2023 ). On the other hand, due to the unequal rights between homeowners and renters resulting from discrimination in China's housing system, migrant renters cannot obtain equal access to public services (e.g., children education, healthcare, and social welfare) like migrant owners, which has become a barrier for them to integrate into society in host cities ( Zhong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, it can significantly impact health outcomes through social mentality and perceived stress ( Xia & Ma, 2020 ; Zhou et al, 2022 ). Previous research further found that social integration can also improve migrants' physical health via increasing utilization of health services ( Fei et al, 2023 ). On the other hand, due to the unequal rights between homeowners and renters resulting from discrimination in China's housing system, migrant renters cannot obtain equal access to public services (e.g., children education, healthcare, and social welfare) like migrant owners, which has become a barrier for them to integrate into society in host cities ( Zhong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%